(3MbGFb GdJChjd aj eJTGHg GdJfRjds - (3eMeO Hf GdMSjf Hf ehSi GdQVj GdYdhj GdMSjfj GdehShj, CHh GdMSf GdTQja GdQVj,J (B406 (3g` s
(3ChdgG (B:s
(3GdShQI GdJi jPcQ ajgG Gd YeQGf eSCdI ef SCd Yf eYfi bhdg JYGdi (B( (3gh GdPi CfRd Ydjc GdcJGH ef BjGJg eMceGJ gf Ce GdcJGH hCNQ eJTGHgGJ (B) s
(3BNQgG (B:s
(3eSCdI hef SCd Yf eYfi bhdg JYGdi (B( (3Ef GdPjf caQhG HCjGJfG Sha fUdjge fGQkG cdeG fVLJ LdhOge HdOfGge LdhOkG ZjQgG djPhbhG GdYPGH Ef Gddg cGf YRjR kG McjekG (B) s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ Hbde Hg VHWs
(3bhHdJ gPg GdfSNI s
(3hfbdJ ef fSNI bQFJ Ydi GdeUfa s
(3bQf GdfSN (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs